PENGEMBANGAN KREATIVITAS DAN KOMPETENSI MAHASISWA DALAM MEMPERSIAPKAN PEMBELAJARAN BIOLOGI MATA KULIAH PERENCANAAN PENGAJARAN BIOLOGI - Jalilah Azizah Lubis; Fitri Agustina Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This study aims to find out the planning developed by students eligible to be used as materials for planning in teaching in the field, teaching planning materials taught by SCL (Student-Centered Learning) approach. Knowing the creativity of biology teaching planning with Student-Centered Learning approach, as reference material for students to be developed effectively during Field Lecture Practice (PKL) and improve learning result of teaching planning of biology student. This research is research of thedevelopment of the4D model (four D model) with research procedure covering Define, Design, Develop and Disseminate. The data obtained are quantitative data of observer and qualitative data. Based on the results of the study, the average percentage of the five planning indicators obtained data from the average observer preparation above average teaching that is ≥ 3.00 and categorized